Explorations : - Arny, Thomas (McGraw-Hill, 2008)
Explorations-An Introduction to Astronomy, 5th edition, is built on the foundation of its well known writing style, accuracy, and emphasis on current information. This new edition continues to offer the most complete technology/new media support package available. That technology/new media package includes: 23 Interactives including 17 NEW and 6 originals converted from Java to Flash(located on the text website and Digital Content Manager CD); Online Learning Center (that allows instructors to take their course to the web if they choose); and Starry Night Planetarium Software (packaged free with each new text).